Sustainable Development of Storm-water Systems in African Cities Considering Climate Change. (2015) - De Paola, Francesco; Galdiero, Enzo; Giugni, Maurizio; Pugliese, Francesco
Abstract: The present paper analyses the problem of the sustainable design and development of urban storm-water systems in response to the climate change and anthropic modification. In particular, the work focuses on the case of the African areas that are characterized by high vulnerability towards these issues. A disaggregation procedure is adopted to estimate the Intensity-Duration-Frequency (IDF) due to climate change starting from daily rainfall data. An integrated approach is used which combines an optimization algorithm (Harmony Search) and a hydraulic simulator to carry out the optimal design of intervention strategies with low economic impact. The methodology is described and discussed with reference to a case study located in the city of Dar es Salaam (Tanzania).